"Shortly afterwards we heard the sound of the gas van": Survivor Testimony and the Writing of History in Socialist Yugoslavia - Byford, Jovan (History & Memory, 2010)
The article examines the assertion found in post–World War II Yugoslav historiography, that a mobile gas van was deployed in Nazi-occupied Serbia not just at the Semlin Judenlager in Belgrade but also at another camp in the city, Banjica. This claim is based on a small number of contradictory testimonies, mainly from survivors, which were collected by local institutions after the war. How can we explain the presence of this by all accounts erroneous claim in the testimonies of survivors? Why and how was it incorporated into the camp's history in spite of the glaring inconsistencies and the absence of corroborating evidence? The article argues that individual memories of the gas van encountered in the testimonies, and their subsequent assimilation into the historical memory of the war, are both products of the same dynamic, namely the socially mediated and institutionally embedded nature of "witnessing."